Storage and Teaching Courses Computing Documentary, Visitors Information Science and Technology and Training Audiovisual Collection - Chacón Alvarado, Lucía (1992)
In the cycle of Professional Conferences the M.I.L.S. Lucía Chacón Alvarado of the School of Librarianship, Documentation and Information of the National University of Costa Rica, presents her paper with the theme "The Management of Information in Specialized Areas in Cosa Rica".